Investigation of the Er: YAG laser and diamond bur cavity preparation on the marginal microleakage of Class V cavities restored with different flowable composites. Issue 5 (23rd January 2017) - Tuna, Elif Bahar; Ozel, Emre; Kasimoglu, Yelda; Firatli, Erhan
Abstract: The purpose of this study was to evaluate the efficiency of the Er:YAG laser and diamond bur cavity preparation on the marginal microleakage of Class V cavities. Group 1: bur preparation (bp) + Vertise Flow (VF); Group 2: laser preparation (lp) + VF; Group 3: bp + Adper Easy One (AEO) + Filtek Ultimate Flowable Composite (FUFC); Group 4: lp + AEO + FUFC; Group 5: bp + Clearfil S3 Bond (CSB) + Clearfil Majesty Flow (CMF); Group 6: lp + CSB + CMF. Data were analyzed by Kruskal–Wallis and Mann–Whitney U tests ( p  < .05). More microleakage was observed in cervical regions compared to occlusal regions in all groups ( p  < .05). No significant difference was observed among all groups in terms of occlusal and cervical surfaces, respectively ( p  > .05). The use of the Er:YAG laser for cavity preparation with different adhesive systems and flowable composites did not influence microleakage. Abstract : Scanning electron microscope image at 1000 magnification for self‐adhering light‐cured resin composite (Vertise Flow) group prepared with Er:YAG laser (200 mJ, 20 Hz). Cavosurface margins produced by Er:YAG laser irradiation presents quite a rough appearance (HL: Hybrid Layer, C: Composite, D: Dentin).